Facts and fears eaudiobook Hard truths from a life in intelligence. - Clapper, James R. (Penguin Audio, 2018)
New York Times bestseller The former Director of National Intelligence's candid and compelling account of the intelligence community's successes—and failures—in facing some of the greatest threats to America When he stepped down in January 2017 as the fourth United States director of national intelligence, James Clapper had been President Obama's senior intelligence adviser for six and a half years, longer than his three predecessors combined. He led the U.S. intelligence community through a period that included the raid on Osama bin Laden, the Benghazi attack, the leaks of Edward Snowden, and Russia's influence operation during the 2016 U.S. election campaign. In Facts and Fears , Clapper traces his career through the growing threat of cyberattacks, his relationships with presidents and Congress, and the truth about Russia's role in the presidential election. He describes, in the wake of Snowden and WikiLeaks, his efforts to make intelligence more transparent and to push back against the suspicion that Americans' private lives are subject to surveillance. Finally, it was living through Russian interference in the 2016 presidential election and seeing how the foundations of American democracy were—and continue to be—undermined by a foreign power that led him to break with his instincts honed through more than five decades in the intelligence profession to share his inside experience. Clapper considers such controversial questions as, Is intelligence ethical? Is it moral to intercept communications or to photograph closed societies from orbit? What are the limits of what we should be allowed to do? What protections should we give to the private citizens of the world, not to mention our fellow Americans? Are there times when intelligence officers can lose credibility as unbiased reporters of hard truths by inserting themselves into policy decisions? Facts and Fears offers a privileged look inside the U.S. intelligence community and, with the frankness and professionalism for which James Clapper is known, addresses some of the most difficult challenges in our nation's history.